"Working things out": a back-stage examination of museum documentation. (3rd July 2021) - Tran, Quoc-Tan
ABSTRACT: The virtuality and materiality of the digital have created new opportunities for museums to facilitate modes of collaboration and participation centered on marginal actors who were previously ignored or uninvolved in the construction of the social worlds they inhabit. This article examines the limits and fragility of one such mode of participation: museum documentation work. Drawing on staff interviews at the Museum of European Cultures in Berlin, the article investigates how the daily practices of museum staff shape work-related arrangements that support institutional memory-making. In focusing on the infrastructure qualities hidden away in the museum's back-stage operations, the article reveals the political stakes of repair and directs attention to the relationality of workplace order. The article contends that, while documentation is the backbone of the museum's informational fabric, it is frequently done and figured out by implicated actors, and performed within the entangled back-stage setting of museum work.